Perspectives of the sarcoma clinical nurse consultant role: A qualitative study. Issue 4 (August 2021) - Weaver, Rhys; O'Connor, Moira; Ngune, Irene; Smith, Richard Carey; Phillips, Jane; Halkett, Georgia
Abstract: Background: Patients diagnosed with sarcoma experience complex treatment pathways and unmet needs. The Sarcoma Clinical Nurse Consultant position was recently established in Western Australia to improve the quality of patient care. As this role is new in Western Australia and nationally, research is required to understand the duties, benefits, and gaps of the position. Aim: To explore patients', carers', and health professionals' perspectives of the role of the Sarcoma Clinical Nurse Consultant in Western Australia. Methods and design: The study employed a qualitative research design with semistructured interviews. Participants included: Patients diagnosed with sarcoma ( n = 20), their family carers ( n = 14), and health professionals working with people diagnosed with sarcoma ( n = 21). Transcripts were analysed using thematic analysis. Findings: Four overarching themes were identified: (i) multiple responsibilities; (ii) inconsistent contact with the sarcoma nurse; (iii) the importance of the role; and (iv) lack of support for the sarcoma nurse. The Sarcoma Clinical Nurse Consultant was considered central to improving patient care, however, the position appeared to be inadequately supported at a systems' level. Discussion: The Sarcoma Clinical Nurse Consultant role is essential to the delivery of evidence based patient-centred sarcoma care and support, coordinated care, and service improvement. Conclusion: The Sarcoma Clinical Nurse Consultant position should be supported with administrative support and support nurse positions so they can focus on clinical duties and providing patient support. Given this is a new and emerging role, it is critical that sarcoma services regularly review and evaluate these positions and ensure that they are adequately supported.